Physiological quality of sunflower seeds stored in different packaging - Smaniotto, Thaís Adriana Souza (2020)
The production of vigorous seeds, which achieve high yields, has been a common desire among farmers, seed quality is still determined within the field.  However, the post-harvest stages play an important role in maintaining this quality so that the feasibility remain until the consumption of this product. Therefore, it is extremely important to carry out studies that involve the dynamics between drying, storage and packaging to establish the best way of conducting this storage period in order to maintain the physiological aspects of the seeds. In this study, the objective was to evaluate the physiological quality of sunflower seeds stored in different packages for 270 days. Seeds with a moisture content of 7.9% (wb) were packed in paper bags, polypropylene containers, high density polyethylene bottles (HDPB) and reused polyethylene terephthalate (PT) bottles, which were kept at ambient conditions for 270 days. Every 90 days the seeds were evaluated for moisture content, electrical conductivity, germination, germination speed index, normal seedlings and dry mass of normal seedlings. The packaging and storage time influence the physiological quality of sunflower seeds. It is concluded that paper packaging promotes better maintenance of the physiological quality of sunflower seeds.